Case report: A new treatment for restless leg syndrome: three cases - Li, Ying; Zhang, Wenjing; Wang, Hui; Zhang, Weiwei (Frontiers in Neuroscience, 2024)
Restless legs syndrome is a movement disorder that seriously affects the quality of life of patients. It is characterized by marked discomfort mainly occurring in the deep tissues of the lower extremities, including deep muscle or bone chafing, as well as crawling sensations or pulling sensations. These sensations often cause patients to awaken after falling asleep and to feel the urge to walk around, which seriously affects their sleep quality. Patients with restless leg syndrome exhibit significantly enhanced sympathetic nerve activity and immune disorders, while stellate ganglion blockage can block sympathetic nerves and regulate immune cells and cytokines to maintain immune system homeostasis. We report three patients with restless legs syndrome complicated with severe nephrotic syndrome. After treatment with stellate ganglion block, the symptoms in the restless legs were relieved within 1 month, and the quality of sleep was significantly improved. Our findings suggest that stellate ganglion block has broad promise in the management of restless legs syndrome patients with severe comorbidities.